Ant Colony Optimized Routing Strategy for Electric Vehicles. (24th September 2018) - Joo, Hyunjin; Lim, Yujin
Abstract : Electric vehicles (EVs) have recently attracted increasing research interest, on account of environmental issues and diminishing fuel reserves. EVs are environmentally friendly but have a short driving range. EVs must utilize energy efficiently, because they travel with limited energy. Conventional vehicle routing methods are not suitable for EVs, as they do not take energy consumption into account. This study introduces an energy efficient routing method using ant colony optimization (ER-ACO) to maximize the energy efficiency. We simulated ER-ACO and compared it with other ACO techniques, including the conventional routing method and other approaches for EVs. As a result, the proposed model improved the energy efficiency in terms of both the average distance per kW and average energy consumption.